Gait asymmetry is associated with performance-based physical function among adults with lower-limb amputation. (18th November 2022) - Seth, Mayank; Coyle, Peter C; Pohlig, Ryan T; Beisheim, Emma H; Horne, John R; Hicks, Gregory E; Sions, Jaclyn Megan
ABSTRACT: Background: Adults with lower-limb amputation walk with an asymmetrical gait and exhibit poor functional outcomes, which may negatively impact quality-of-life. Objective: To evaluate associations between gait asymmetry and performance-based physical function among adults with lower-limb amputation. Methods: A cross-sectional study involving 38 adults with a unilateral transtibial (N = 24; 62.5 ± 10.5 years) or transfemoral amputation (N = 14; 59.9 ± 9.5 years) was conducted. Following gait analysis (capturing step length and stance time asymmetry at self-selected (SSWS) and fast walking speeds (FWS)), participants completed performance-based measures (i.e. Timed Up and Go (TUG), the 10-Meter Walk Test (10mwt), and the 6-Minute Walk Test (6MWT)). Results: Step length and stance time asymmetry (at SSWS and FWS) were significantly correlated with each performance-based measure ( p < .001 to p = .035). Overall, models with gait measures obtained at SSWS explained 40.1%, 46.8% and 40.1% of the variance in TUG-time ( p = .022), 10mwt-speed ( p = .003) and 6MWT-distance ( p = .010), respectively. Models with gait measures obtained at FWS explained 70.0%, 59.8% and 51.8% of the variance in TUG-time ( p < .001), 10mwt-speed ( p < .001), and 6MWT-distance ( p < .001), respectively. Conclusions: Increases in step length or stance time asymmetry are associated with increased TUG-time, slower 10mwt-speed, and reduced 6MWT-distance. Findings suggest gait asymmetry may be a factor in poor functional outcomes following lower-limb amputation.